Noradrenaline as a key neurotransmitter in modulating microglial activation in stress response. (February 2021) - Sugama, Shuei; Kakinuma, Yoshihiko
Abstract: State of mind can influence susceptibility and progression of diseases and disorders not only in peripheral organs, but also in the central nervous system (CNS). However, the underlying mechanism how state of mind can affect susceptibility to various illnesses in the CNS is not fully understood. Among a number of candidates responsible for stress-induced neuroimmunomodulation, noradrenaline has recently been shown to play crucial roles in the major immune cells of the brain, microglia. In particular, recent studies have demonstrated that noradrenaline may be a key neurotransmitter in modulating microglial cells, thereby determining different cell conditions and responses ranging from resting to activation state depending on host stress level or whether the host is awake or asleep. For instance, microglia under resting conditions may have constructive roles in surveillance, such as debris clearance, synaptic monitoring, pruning, and remodeling. In contrast, once activated, microglia may become less efficient in surveillance activities, and instead implicated in detrimental roles such as cytokine or superoxide release. It is also likely that glial activation, both astrocytes and microglia, are negatively associated with the clearance of brain waste via the glymphatic system. In this review, we discuss the possible underlying mechanism as well as the roles of stress-induced microglial activation. Highlights: This review discusses the mechanism of stress-induced microglial activation. Noradrenaline may determine various conditions of microglia. Activated microglia may become less efficient in the surveillance activities. Glial activation may be negatively associated with glymphatic system activity. Microglial inhibition may be helpful in the treatment of neurological disorders.